2010
DOI: 10.1002/jclp.20753
|View full text |Cite
|
Sign up to set email alerts
|

Resistance/Reactance Level

Abstract: Psychotherapists from all professions and perspectives periodically struggle to effectively manage a patient's resistance to change. This article provides definitions and examples of patient-treatment matching applied to patient resistance or reactance. We report the results from an original meta-analysis of 12 select studies (N = 1,102) on matching therapist directiveness to patient reactance. Our findings support the hypothesis that patients exhibiting low levels of trait-like resistance respond better to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
104
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 26 publications
3
104
0
2
Order By: Relevance
“…If therapists respond to a clients' RPMs by insisting that they revise their maladaptive selfnarrative or by trying to convince them that they are changing, the clients may feel misunderstood, invoking a "strong reactance on the part of the client, often hardening the client's stuck position" (Engle & Arkovitz, 2008, p. 390). This is consistent with research suggesting that higher levels of therapist demand or directiveness toward change are associated with higher levels of client resistance, whereas more supportive approaches diminish resistance (Miller, Benefield, & Tonigan, 1993;Patterson & Forgatch, 1985; see also Beutler, Harwood, Michelson, Xiaoxia, & Holman, 2011, for a metaanalysis of the interaction between client reactance and therapist directiveness).…”
Section: Discussionsupporting
confidence: 86%
“…If therapists respond to a clients' RPMs by insisting that they revise their maladaptive selfnarrative or by trying to convince them that they are changing, the clients may feel misunderstood, invoking a "strong reactance on the part of the client, often hardening the client's stuck position" (Engle & Arkovitz, 2008, p. 390). This is consistent with research suggesting that higher levels of therapist demand or directiveness toward change are associated with higher levels of client resistance, whereas more supportive approaches diminish resistance (Miller, Benefield, & Tonigan, 1993;Patterson & Forgatch, 1985; see also Beutler, Harwood, Michelson, Xiaoxia, & Holman, 2011, for a metaanalysis of the interaction between client reactance and therapist directiveness).…”
Section: Discussionsupporting
confidence: 86%
“…impulsivity is associated with chronic substance use; Moeller and Dougherty, 2002) and require targeted interventions (e.g. reactant/resistant patients respond better to non-directive approaches; Beutler et al, 2011). Consistent with the evidence, these treatment approaches guide clinicians on how to adapt language, questioning techniques, therapeutic style (e.g.…”
mentioning
confidence: 88%
“…Such reactance may even change throughout treatment; for example, some patients may be initially reactant at fi rst but, after seeing initial gains, become more amenable to a higher level of therapist directiveness. These principles also apply throughout other components of treatment (e.g., psychoeducation, cognitive restructuring; Beutler et al, 2011 ) . In this way, it is not just what a clinician delivers (i.e., CBT for anxiety) but also how he/ she delivers it that leads to effective therapistpatient match.…”
Section: Treatment Approaches To Address Therapist-patient Mismatchmentioning
confidence: 99%
“…Thus, a patient who is high on reactance would match poorly with a therapist who takes an authoritative stance, while a patient low in reactance may match poorly with a therapist who is well meaning in a collaborative style but does not provide suf fi cient direction. Over a variety of treatments, it has been observed that patients high in reactance bene fi t from less structured treatment, while those in low reactance bene fi t from more therapist guidance and structured therapy (Beutler, Harwood, Michelson, Song, & Holman, 2011 ) . The implications of these fi ndings quickly become pertinent in CBT for anxiety, given that patients sometimes require urging by clinicians to engage in exposures.…”
Section: Therapist-patient Mismatchmentioning
confidence: 99%